Black esophagus: exploring the dark - Robert Forster; Délcio Aparecido Durso; Edoardo Filippo de Queiroz Vattimo; Luis Massuo Maruta; Ana Luiza Werneck-Silva; Vilma Takayasu; Marcia Yoshie Kanegae; Fabiana Roberto de Lima (University of São Paulo, 2013)
Black esophagus is a rare but underdiagnosed disease. It occurs most frequently in severely ill patients and carries a high mortality rate. Cause of death is usually attributed to the comorbid conditions. Treatment is directed at the underlying cause, acid suppression and keeping the patient nil-per-os. Surgery is needed in complicated cases and stenosis is the most feared longterm sequel. In the present article, two cases are described and literature is reviewed.